Antiretroviral postnatal prophylaxis to prevent HIV vertical transmission: present and future strategies. Issue 2 (20th February 2023) - Penazzato, Martina; Kasirye, Ivy; Ruel, Theodore; Mukui, Irene; Bekker, Adrie; Archary, Mohendran; Musoke, Philippa; Essajee, Shaffiq; Siberry, George K.; Mahy, Mary; Simnoue, Daniele; Simione, Beatriz; et al.
Abstract: Introduction: Maternal antiretroviral therapy (ART) with viral suppression prior to conception, during pregnancy and throughout the breastfeeding period accompanied by infant postnatal prophylaxis (PNP) forms the foundation of current approaches to preventing vertical HIV transmission. Unfortunately, infants continue to acquire HIV infections, with half of these infections occurring during breastfeeding. A consultative meeting of stakeholders was held to review the current state of PNP globally, including the implementation of WHO PNP guidelines in different settings and identifying the key factors affecting PNP uptake and impact, with an aim to optimize future innovative strategies. Discussion: WHO PNP guidelines have been widely implemented with adaptations to the programme context. Some programmes with low rates of antenatal care attendance, maternal HIV testing, maternal ART coverage and viral load testing capacity have opted against risk‐stratification and provide an enhanced PNP regimen for all infants exposed to HIV, while other programmes provide infant daily nevirapine antiretroviral (ARV) prophylaxis for an extended duration to cover transmission risk throughout the breastfeeding period. A simplified risk stratification approach may be more relevant for high‐performing vertical transmission prevention programmes, while a simplified non‐risk stratified approach may be more appropriate for sub‐optimally performing programmes given implementation challenges. In settings with concentrated epidemics, where the epidemic is often driven by key populations, infants who are found to be exposed to HIV should be considered at high risk for HIV acquisition. All settings could benefit from newer technologies that promote retention during pregnancy and throughout the breastfeeding period. There are several challenges in enhanced and extended PNP implementation, including ARV stockouts, lack of appropriate formulations, lack of guidance on alternative ARV options for prophylaxis, poor adherence, poor documentation, inconsistent infant feeding practices and in inadequate retention throughout the duration of breastfeeding. Conclusions: Tailoring PNP strategies to a programmatic context may improve access, adherence, retention and HIV‐free outcomes of infants exposed to HIV. Newer ARV options and technologies that enable simplification of regimens, non‐toxic potent agents and convenient administration, including longer‐acting formulations, should be prioritized to optimize the effect of PNP in the prevention of vertical HIV transmission.